Reversal and prevention of deregulated autophagy in cutaneous autoimmune disorders—a pilot study on vitiligo with nutrigenomics based approach of “Maximum Nutrition and Minimum Medication” - Suruchi Garg; Murlidhar Rajagopalan; Anupa Mary George; Hemangi Parwani; Titiksha Hans (Pigment International)
AbstractNutritional status of patients, specially prolonged starvations is an important sub-component of the environmental factors, speculated to have indirect impact on the initiation, propagation, resolution, and exacerbation stages of autoimmunity. The study was based on the hypothesis of conscious, selective, and self-destruction, that is, deregulated autophagy of skin and hair in low dietary protein scenario triggered with prolonged starvations. It was aimed to reverse the self-destruction/deregulated autophagy by providing early morning, low carb-high protein nutrition, and correcting underlying micronutrient deficiency and studying its effect on reducing auto-immunity and eventually reducing disease burden and recurrence. Methods: In this retrospective study, patients were divided into two categories based on disease activity and nutrition. Group A: “novice group” of vitiligo patients who presented at an early stage of their disease were managed with basic standard of therapeutics. Group B: “stabilized group” of vitiligo who were given surgical treatment and followed up for 3 years for any recurrences. Personalized diet plan aimed at reversing high carb-low protein diet and avoiding prolonged overnight starvation adhering to early morning breakfast respecting the circadian rhythm and balanced with additional plant based protein was advised. All detectable underlying micronutrient deficiencies were corrected. Results: Thirty patients were enrolled in the study, 20 in group A and 10 in group B. We observed visible signs of improvement in group A, with early vitiligo (90%) with topical therapy and nutritional intervention as early as 3 weeks. Following surgical procedure in group B, 50% patients had near complete pigmentation at the end of 3 months and 30% within next 3 months. At the end of 6 months, all patients had significant improvement in VASI and VIDA score, however two patients in each group had recurrence at end of 1 year who deviated from nutritional protocol and were found to be deficient in protein intake and micronutrients deficiency was detected on blood investigation. The improvement in VASI scores with conventional treatment and nutritional intervention was found to be statistically significant at 6 months and 1-year interval in group A with paired t test (P = 0.013). Similarly, improvement in VASI was statistically very significant at 6 months and 1-year duration in surgically treated vitiligo group B (P = 0.001). These patients were put on immunosuppressive therapies in first group after correction of deficiencies and managed with supportive and conventional therapy in second group in subsequent 3 years follow up. Conclusion: Nutritious diet aimed at correction of underlying protein and micronutrient deficiency with special emphasis on circadian rhythm may arrest the natural progression of disease at an early stages of the disease and prime the body for oral immunosuppressive drugs. This approach may prevent the recurrence in patients already stabilized with standard care of therapeutics and surgery in future.